2001
DOI: 10.1006/jmaa.2001.6705
|View full text |Cite
|
Sign up to set email alerts
|

Semigroups and Linear Partial Differential Equations with Delay

Abstract: We prove the equivalence of the well-posedness of a partial differential equation with delay and an associated abstract Cauchy problem. This is used to derive sufficient conditions for well-posedness, exponential stability and norm continuity of the solutions. Applications to a reaction-diffusion equation with delay are given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
95
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 34 publications
2
95
0
Order By: Relevance
“…Dropping the assumption that B is bounded, Liu ([Liu]) showed that if A generates a holomorphic semigroup and B is (−A) α -bounded, then the exponential stability of (1.1) (with τ (t) ≡ r) on the phase space C(−r, 0; D(A)) is robust. Bátkai et al ([Ba1,Ba2]) proved a similar result on the phase space X × L p (−r, 0; D(B)).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Dropping the assumption that B is bounded, Liu ([Liu]) showed that if A generates a holomorphic semigroup and B is (−A) α -bounded, then the exponential stability of (1.1) (with τ (t) ≡ r) on the phase space C(−r, 0; D(A)) is robust. Bátkai et al ([Ba1,Ba2]) proved a similar result on the phase space X × L p (−r, 0; D(B)).…”
mentioning
confidence: 71%
“…The robustness of delay equations has been studied by many authors (see cf. [Ba1,Ba2,Da,EN,Hu,FN,JGH,Liu]). …”
mentioning
confidence: 99%
“…It is shown in [2] that the delay equation (DE) is equivalent to an abstract Cauchy problem U (t) = AU(t) (t 0),…”
Section: Introductionmentioning
confidence: 99%
“…Almost at the same time as [15], Schliichtermann [14] proved that both the space of weakly compact operators and the space of conditionally weakly compact 412 X. Song and J. Peng [2] operators enjoy the property. Moreover, he remarked that the mentioned conclusions can be extended to the nonlinear case if the uniform boundedness in Voigt's definition of the strong convex compactness property is replaced with the uniform integrability property (see, [14,Remark 2.4] or (2.3) below).…”
Section: Introductionmentioning
confidence: 86%
“…If the perturbation operator K is linear, then it is easy to show that so is the perturbed semigroup {S t } t^ o whenever the unperturbed semigroup {T t }t% o is strongly continuous or weakly completely continuous. See [2,5,6,7,8,11] for details about property persistence of operator semigroups under linear perturbation. However, in the nonlinear case, we do not know if the perturbed {S t }t% o inherits the weak continuity, strong continuity or weakly complete continuity of the unperturbed semigroup…”
mentioning
confidence: 99%